Immigration and Victimization in Adolescence and Adulthood: Findings from a Nationally Representative Sample - Mammadov, Rashad (Victims & offenders, 2021)
There has been a considerable amount of research examining the potential connection between immigration and the risk for victimization. The results generated from this body of research have produced somewhat mixed results, with some research showing an association and other research failing to detect an association. The current study sought to add to this existing knowledge base by examining the potential association between being an immigrant and being victimized during adolescence and adulthood. To do so, the authors analyzed data drawn from the National Longitudinal Study of Adolescent to Adult Health. Analyses of these data revealed that being an immigrant was unrelated to 11 measures of victimization, including repeat victimization, drawn from four waves of data. There were no results indicating that immigration and victimization were associated. We conclude by discussing the limitations of the study and avenues for additional research addressing the association between immigration and victimization.